The internal heavy-atom effect on 3-phenylselanyl and 3-phenyltellanyl BODIPY derivatives studied by transient absorption spectroscopy. Issue 2 (21st January 2016) - Al Anshori, Jamaludin; Slanina, Tomáš; Palao, Eduardo; Klán, Petr
Abstract : The extent of intersystem crossing related to the heavy-atom effect of Se and Te atoms was investigated on monosubstituted 3-phenylselanyl and 3-phenyltellanyl BODIPY derivatives. Abstract : Three monosubstituted 3-phenylselanyl and 3-phenyltellanyl BODIPY derivatives were synthesized and their spectroscopic properties were characterized and compared to those of iodine and chlorine-atoms containing analogues as well as an unsubstituted BODIPY derivative. The fluorescence quantum yields were found to decrease, whereas the intersystem crossing quantum yields ( Φ ISC ), determined by transient spectroscopy, increased in the order of the H → Cl → Se/I → Te substitution. The maximum Φ ISC, found for the 3-phenyltellanyl derivative, was 59%. The results are interpreted in terms of the internal heavy-atom effect of the substituents.